Hubungan Infeksi Soil-Transmitted Helminths (STH) dengan Angka Kejadian Tuberculosis (TB) pada Balita Stunting di Kecamatan Rambipuji - Ayundasari, Asti; Hermansyah, Bagus; Nurmaida, Eny; Utami, Wiwien Sugih; Armiyanti, Yunita; Sulistyaningsih, Erma (Faculty of Medicine, Universitas Andalas, 2024)
Infection is one of the factors associated with stunting. The relationship between stunting and infection can have reciprocal effects. Stunting can increase the risk of infection. Conversely, infections such as Soil-Transmitted Helminths (STH) and Mycobacterium tuberculosis (M. tuberculosis) can also increase the risk of stunting. Objective: To analyzed the correlation between STH infection and the incidence of tuberculosis (TB) in stunting toddlers. Methods: The subjects of this study were 108 stunting toddlers obtained from a simple random sampling method. It was conducted from May 2023 to March 2024 in several villages within the Rambipuji District of Jember Regency, including Gugut, Rambigundam, Pecoro, and Kaliwining. The statistical analysis used in this study was the contingency coefficient test. Results: Findings revealed that the occurrence of STH infection with TB in stunting toddlers was 0%. Conclusion: There is no statistically significant relationship between STH infection and the incidence of TB in stunting toddlers in the Rambipuji District, Jember Regency.Keywords: soil-transmitted helminths, tuberculosis, stunting